ON THE EYE DIAMETER - TOTAL LENGTH RELATIONSHIP OF THE INDIAN MACKEREL RASTRELLIGER KANAGURTA (CUVIER) - UDUPA, K S; BHAT, C. H KRISHNA (Fishery Technology, 2017)
791 mackerel along the coast Karnataka during 1979-80 season was studied for total length-eye diameter relationship. It was found that mackerel having the eye diameter range 0.5 to 0.9 cm belong to 1 year old group, 1.0 to 1.2 cm to 2 year old group and 1.3 to 1.5 cm to 3 year old group. Among the many morphemetric characters, eye diameter of fish has attracted little attention in the field of fishery research. When compared to other morphometric characters, eye diameter seems to have no significant role to play in taxonomical work. The present note aims in correlating the eye diameter of the Indian u ackerel R. kanagurta to total length and hence to age of the fish.